Wellbeing during a pandemic: An empirical research examining autonomy, work-family conflict and informational support among SME employees - Zakhem, Najib Bou; Farmanesh, Panteha; Zargar, Pouya; Kassar, Abdulnasser (Frontiers in Psychology, 2022)
Numerous sectors were severely affected by the occurrence of Covid-19 pandemic. Individuals working in different industries were forced to change their work environments to their homes, leading to conflict between work and family. As a result, performance and wellbeing of employees of small and medium enterprises were diminished. Within the scope of Frontiers call for research “Workplace effects of Covid-19 on employees”, this research emphasizes on the positive impact of job autonomy that can reduce conflicts between work and family. Furthermore, organizations carry a major role by providing informational support that equips employees with awareness required to handle uncertain times. Through a survey, 198 participants provided empirical data that was analyzed using modern analytical methods. While highlighting important elements related to performance and overall wellbeing of employees, the current findings can be beneficial for managers of small and medium enterprises.